Hipoteza – krzywa wiedzy dziecka - Kamil Stępień; Bogdan Stępień (Problemy Wczesnej Edukacji)
The authors checked the results of the final primary school exam of 3 million Polish students in the years 2005–2013. This research confirms the influence of the age of entering education on the student’s results and the chance of repeating a school year. This paper presents only a sample of the research, supported by a hypothesis of a student’s knowledge curve.